Response of seed germination and seedling growth of perennial ryegrass (Lolium perenne L.) to drought, salinity, and pH in Karst regions - Rui Wang; Yuting Yang; Xiangtao Wang; Junqin Li; Yang Gao; Haiyan Huang; Zijun Zhou; Puchang Wang; Lili Zhao (Scientific Reports)
Abstract Seed germination and seedling growth are crucial for the successful establishment and reproduction of plants in heterogeneous environments, especially in the ecologically fragile karst regions. Despite the ecological importance of perennial ryegrass (Lolium perenne L.) as a forage resource and its role in mitigating rocky desertification, studies addressing the effects of karst-specific environmental factors on its early growth stages are limited. This study is the first to simulate karst soil conditions to evaluate the impacts of drought (0–0.53 MPa), salinity (0–150 mM), and pH (pH 3–9) on seed germination and seedling growth of perennial ryegrass. The results showed that under different drought stresses, water potentials ranging from 0 to − 0.32 MPa had no significant effect on seed germination. However, water potentials of − 0.06 MPa and − 0.17 MPa significantly promoted root and shoot growth, as well as increased biomass. In the salt stress experiment, CaCl2 concentrations of 5–10 mM favored seed germination; specifically, 5 mM CaCl2 increased the germination rate to 96.5%, and root and shoot lengths exceeded those of the control. pH levels ranging from 3 to 9 had little effect on germination, but extremely acidic conditions (pH 3) significantly inhibited root and shoot elongation. Therefore, optimal growth conditions were determined to be drought stress from 0 to − 0.17 MPa, calcium salt stress from 0 to 25 mM, and a pH of 4 to 9. These findings identify optimal growth conditions for perennial ryegrass, providing a scientific basis for seed cultivation, pasture management, and ecological restoration in karst regions. Our study contributes to the understanding of plant responses to environmental stresses in karst systems and supports sustainable agricultural and conservation practices.